EDUKASI PENYAKIT HIPERTENSI, ASAM URAT DAN DIABETESPADA WARGADUSUNNGEPUH LOR, DESA BANYUSIDI, PAKIS, MAGELANG,JAWA TENGAH - Muhammad Hasyim (UII, 2014)
Health is the most important thing that must be kept by humans. In the past,people more die due to infectious diseases such as diarrhea, malaria, and hepatitisbecause of its spread are difficult to control cause of a lack of knowledge of the disease.It has shifted, now usually non-infectiousdiseases that cause more people who died ashypertension, diabetes and heart disease. This is due to the lack of public knowledgeand unhealthy lifestyle that society needs to recognize andprevent this disease with thereset of lifestyle change. This educational outreach programs and provide insight onNgepuh Lor Dusun community to be able to regularly check their health and maintaintheirhealth.